Anodic Polarization of Mild Steel in Saturated C a(OH)2 Contaminated with NaCl in Presence of NaNO2 - S. Yaro, Aprael; S. Hassan, Hany (Iraqi Journal of Chemical and Petroleum Engineering, 2007)
The corrosion  behavior  of mild sleet  in saturated  aerated  and de-aerated  Ca(OH)2 solution  was  investigated  using electrochemical measurements. The work was carried out with small coupons immersed in solutions containing different quantities of NaCl in presence of various NaN02 concentrations as corrosion inhibitors. It has been found thal:(1 ) In presence  of NaCl,  the time required  to reach O2  evolution potential  in de-aerated  Ca(OH)2 polarized  at  10μA/cm 2 is function of inhibitor concentration and it becomes lass as NaN02 increases compared with zero presence indicating the effectiveness of NaN02 as anodic corrosion  inhibitor. (2) In absence of NaCl, the Lime required to reach O2 evolution potential in de-aerated solutions is less that in aerated solutions when inhibitor increases from 0 to 0.3 wt. %. (3) In presence  of sufficient  chloride in de-aerated Ca(OH)i solution, the passive film  may broken down locally.